Characteristics of the atmospheric boundary layer and its relation with PM2.5 during haze episodes in winter in the North China Plain. (15th February 2020) - Li, Qianhui; Wu, Bingui; Liu, Jingle; Zhang, Hongsheng; Cai, Xuhui; Song, Yu
Abstract: Interactions between the spatiotemporal distribution of pollutants and the structure of the atmospheric boundary layer were studied using data obtained by GPS (Global Positioning System) sounding balloons in an intensive observation period from December 2018 to January 2019 at the Dezhou experimental station in the North China Plain. Under haze weather conditions, negligible variation or a slight increase in temperature, higher relative humidity (RH) and lower wind speed with uncertain wind direction are common characteristics. The concentration distribution of particulate matter ≤2.5 μm ( PM 2.5 ) has a close relationship with the inversion layer, which contributes to the accumulation of PM 2.5 in the lower atmosphere. The reduction of pollutants suspended in the upper layer during haze periods is closely related to low-level jets and intermittent turbulence. Higher RH values are also favourable for the formation of heavy haze, and the value of PM 2.5 increases with an increase in humidity. During hazy days, the heat fluxes and turbulent kinetic energy (TKE) are much smaller than those during clear days. The values of the average maxima of net radiation, sensible heat flux, and latent heat flux are 154, 76, and 15 W / m 2, respectively, and the value of TKE is approximately 0.67 m 2 / s 2 . The decrease in atmospheric boundary layer height (ABLH) is caused by weaker turbulent transfer during haze episodes. The ABLH is approximately 400 m during the daytime and 240 m at night. The power function relationship is shown by a negative correlation between the ABLH and surface PM 2.5 concentration in the convective boundary layer. Highlights: PM 2.5 concentration profiles were collected by GPS sounding balloons in winter. The influence of the ABL structure on PM 2.5 distribution is explained. The scavenging effect of low-level jets on PM 2.5 in the upper layer is confirmed. Heavily polluted layers were discovered at high altitudes and explained.